SO2F2-mediated transformation of 2'-hydroxyacetophenones to benzo-oxetes - Revathi Lekkala; Ravindar Lekkala; Balakrishna Moku; K. P. Rakesh; Hua-Li Qin (Beilstein Journal of Organic Chemistry, 2019)
A catalyst-free novel and efficient methodology for the challenging synthesis of benzo-oxetes from 2'-hydroxyacetophenones mediated by sulfuryl fluoride (SO2F2) gas has been realized. The combination of 2'-hydroxyacetophenones and SO2F2 furnishes synthetically challenging benzo-oxetanes in moderate to excellent yields. The highlight of this work is the design and synthesis of strained four-membered oxete rings.